Finite element modelling and updating for the dynamic behaviour of a structure with bolted joints / Rohaizat Omar - Omar, Rohaizat (2022)
Bolted joints are widely used in various industries for assembling structural components because they are easy to assemble and disassemble, simple to configure and cost-effective. However, the presence of bolted joints in an assembled structure significantly changes the dynamic behaviour of the structure, which are natural frequencies and mode shapes. This change is due to two main factors, namely the stiffness of the contact surfaces and the bolts. These two important factors are not well understood and are very difficult to determine experimentally. To date, no attempt has been made to integrate these factors using FE model updating (FEMU) and experimental modal analysis (EMA) in accurately determining the dynamic behaviour of an assembled structure.